STRATEGI STP DALAM MENINGKATKAN DAYA SAING RUMAH MAKAN PADANG MINANG MURAH DALAM PERSPEKTIF ISLAM - Hanik Listiana; Nila Mayangsari; Puji Rahayu; Mohammad Saiful Rifai (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the implementation of Segmenting, Targeting, and Positioning (STP) strategies in improving the competitiveness of Rumah Makan Padang Minang Murah from an Islamic perspective. The increasing competition in the culinary business sector requires business actors to implement effective marketing strategies in order to maintain customer loyalty and business sustainability. This research employed a qualitative descriptive approach with data collection techniques consisting of interviews, observations, and documentation. The primary data source was obtained from the owner of Rumah Makan Padang Minang Murah. The results of the study indicate that the segmentation strategy focuses on middle-to-lower economic consumers, especially workers and students. The targeting strategy is directed toward loyal customers from the worker and student segments by maintaining food quality and providing good service. Meanwhile, the positioning strategy is implemented by building the image of a Padang restaurant with affordable prices, distinctive taste, and friendly service. From an Islamic perspective, the business has implemented Islamic economic principles such as honesty (ṣidq), justice in pricing, halal product assurance, and avoiding fraudulent practices (gharar). The implementation of STP strategies integrated with Islamic values has proven effective in increasing business competitiveness and maintaining customer loyalty. Therefore, Islamic-based marketing strategies can become an important approach in developing sustainable culinary businesses.